Inoculant machine - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Mobility has now been incorpora ted into the UPIL machine developed by IRAT/CIRAD for on-site production of a leguminous inoculant. This self-contained unit is designed to produce the rhizobium bacteria needed to enable leguminous plants to fix...